1978
DOI: 10.1017/s0043174500064729
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Nitrofen and Oxyfluorfen BetweenPortulaca oleraceaEcotypes and Two Cabbage(Brassica oleraceavar.capitata)Cultivars

Abstract: A collection of common purslane(Portulaca oleraceaL.) ecotypes from various locations around the world was assembled at the University of Illinois. Applications of nitrofen (2,4-dichlorophenyl-p-nitrophenyl ether) to the various ecotypes showed that 3 of the 26 ecotypes [India, Mexico, and Florida (Sanford)] exhibited some degree of tolerance. This marginal tolerance rapidly disappeared as the rate of nitrofen increased beyond 0.56 kg/ha. All of the ecotypes tested were susceptible to applications of oxyfluorf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Any of a wide range of herbicides that disrupt steps in basic cell metabolism is expected to cause damage to the cells, leading to loss of turgor. Gorske and Hopen (1978), have showed that the two herbicides nitrofen and oxyflurofen decreased the water potential in two varieties of cabbage by about two bars, whereas O , Looney and Fry (2005) have reported that a novel herbicide oxaziclomefone inhibited cell expansion in maize without affecting turgor pressure or wall acidification. Many physiological, biochemical and growth parameters were negatively affected by foliar application of five herbicides in cotton and maize seedlings (El Tahir, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Any of a wide range of herbicides that disrupt steps in basic cell metabolism is expected to cause damage to the cells, leading to loss of turgor. Gorske and Hopen (1978), have showed that the two herbicides nitrofen and oxyflurofen decreased the water potential in two varieties of cabbage by about two bars, whereas O , Looney and Fry (2005) have reported that a novel herbicide oxaziclomefone inhibited cell expansion in maize without affecting turgor pressure or wall acidification. Many physiological, biochemical and growth parameters were negatively affected by foliar application of five herbicides in cotton and maize seedlings (El Tahir, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Five herbicides were reported to decrease the turgor pressure in cotton and maize seedlings (El Tahir, 2010). Gorske and Hopen (1978) showed that the two herbicides nitrofen and oxyfluorfen lowered the water potential in two varieties of cabbage by about two bars.…”
Section: Introductionmentioning
confidence: 99%
“…Because these crops are frequently direct-seeded, the ability to apply oxyfluorfen preemergence (PRE) or postemergence (POST) would increase its utility. These methods of applying oxyftuorfen have been evaluated by several researchers but were usually reported to cause unacceptable crop injury (Bhowmik and McGlew 1986;Farnham and Harrison 1997;Gorski and Hopen 1978;Grabowski and Hope 1984;Harrison and Farnham 1998;Herbst andDerr 1990a, 1990b;Johnson et aI., 1992). Herbst andDerr (1990a, 1990b) reported that PRE oxyftuorfen at 0.14, 0.28, and 0.56 kg/ha caused unacceptable delays in broccoli harvest and reduced stands and yields.…”
Section: Introductionmentioning
confidence: 99%
“…POST oxyfluorfen provides good weed control in broccoli and cabbage (Farnham and Harrison 1997;Gorski and Hopen 1978;Grabowski and Hopen 1984;Herbst and Derr 1990a). However, in some instances, the herbicide caused crop injury and reduced yields (Farnham and Harrison 1997;Grabowski and Hopen 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation